Klasifikasi Keuntungan pada Bengkel AS Motor BMW Menggunakan Metode Algoritma C4.5 - Julianto , Julianto; Atika , Prima Dina; Warta , Joni (Journal of Students‘ Research in Computer Science, 2023)
The growth of the motor vehicle and car repair services business is a business that has very high growth in Indonesia, due to the large number of motorized vehicles and cars. Profits in business are important because profits determine whether a company is progressing or not. The method used in this research is Classification Data Mining using the C4.5 Algorithm method, with the attributes involved namely income, cash, spare parts payable, water, electricity, employee salaries, rental costs, consumables, incidental costs, and net income. Algorithm C4.5, which is an algorithm for changing the form of data (tables) into a tree model and then changing the tree model into a rule. The application of the C4.5 algorithm to the profit and loss classification system at workshops was successfully carried out with an accuracy rate of 72.73% from the total data calculation results, and has been implemented in the form of a profit and loss classification application system for website-based workshops. The classification system of advantages and disadvantages in workshops as a result of the research that has been done can be used as a recommendation.